Evaluation of porcine epidemic diarrhea virus in feed manufacturing - Schumacher, Loni Lynn (Kansas State University, 2016)
Biological hazards in animal feed are a growing concern for the feed industry. Porcine epidemic diarrhea virus (PEDV) is the first viral pathogen confirmed to be transmissible in swine feed and feed ingredients. This led to investigations identifying the magnitude of transmissible risk PEDV imposes and strategies to mitigate infectivity in contaminated diets. The objective of the first experiment was to evaluate the minimum infectious dose of PEDV in virus-inoculated feed. Pigs became infected when PEDV concentrations at or above 5.6 × 10¹ 50% tissue culture infectious dose/g (TCID₅₀/g); corresponding feed cycle threshold (Ct) of 37 or below was utilized. Evaluation of a mitigation strategy for PEDV contaminated diets is also important since cross-contamination during feed manufacturing is possible. Therefore, the objective of the second experiment was to determine the effectiveness of feed batch sequencing as a method to minimize the risk of PEDV cross-contamination. This method was effective to reduce but not eliminate infectious PEDV carryover risk. Furthermore, feed that lacked detectible PEDV RNA as analyzed by quantitative real-time reverse transcription PCR assay (qPCR) was infectious. The third study was an observational study complementary to the previous experiment where the magnitude of virus contamination in the feed manufacturing facility was characterized during feed batch sequencing. Widespread contamination of the facility occurred and surfaces remained contaminated until chemically cleaned. The final experiment was conducted to assess PEDV RNA detection in feed and spray dried porcine plasma (SDPP) when analyzed by qPCR across 5 diagnostic laboratories. Overall, it appears qPCR PEDV RNA detection in feed and SDPP was precise as quantified by low coefficient of variation across laboratories, with the exception of one %CV from SDPP inoculated with low virus load from one laboratory. Although the magnitude of the Ct value difference was large in only 1 of 5 laboratories, comparisons of Ct values across laboratories should be interpreted cautiously. Finally, qPCR can be a useful surveillance tool for detection of PEDV RNA in non-clinical samples such as feed and SDPP.
Keywords: Swine; Virus; Sequencing; Feed; Contamination; Bioassay